Analisa Rasio Likuiditas, Profitabilitas, Aktivitas dan Solvabilitas terhadap Capital Gains dan Dividen pada Perusahaan Manufaktur di Bursa Efek Jakarta - Ardi Hamzah (Universitas Kristen Maranatha, 2007)
The objective of this research is to analysis of liquidity, profitability, activity and solvability ratio on capital gains (loss) and dividend at Jakarta Stock Exchange. Investors haveprimarily objective to increase return (capital gains (loss) and dividend) from their investment. The sample of the study are manufacture firms listed in Jakarta Stock Exchange that gave dividend successively for 2001 - 2005. Sample total is 135 firm sample. The result of this study indicate that liquidity, profitability, activity and solvability ratio of the investee company simultanly have significant eject on dividend, while partially only activity ratio have significant eject on dividen. For examine on capital gains (loss) simultanly indicate all ratio have not effect, while partially only liquidity ratio havesignificant eflecr on capital gains (loss). It means that dividend given to the investor by effect liquidity, profitability, activity and solvability ratio, while capital gains (loss) not given to the investor by effect all ratio in research.Keywords : liquidity, profitability, activity, solvability, capital gains (loss), dividend